Gender Innovation as Strategic Dynamic Capability Integrating Intellectual Capital, Cost Management, and FinTech for MSME Sustainability - Etty Harya Ningsi; Putri Wahyuni (Ilomata International Journal of Tax and Accounting, 2026)
This study examines the role of Gender Innovation as a strategic dynamic capability integrating Intellectual Capital, Strategic Cost Management, and Financial Technology (FinTech) to enhance MSME sustainability. Drawing on Dynamic Capability Theory and the Resource-Based View, the study conceptualizes Gender Innovation as an organizational capability that enables firms to sense emerging opportunities through diverse perspectives, seize these opportunities by integrating inclusive knowledge resources into strategic decisions, and transform organizational practices through adaptive managerial and technological innovation. Using a quantitative approach, data were collected from 100 MSMEs in Medan City, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that FinTech adoption significantly influences MSME sustainability, highlighting digital financial integration as a key mechanism for long-term business viability. Gender Innovation significantly strengthens Intellectual Capital and Strategic Cost Management, indicating its role as a higher-order dynamic capability. In this study, Gender Innovation is conceptualized as a second-order construct integrating inclusive managerial practices and innovation orientation through a hierarchical component model. However, Intellectual Capital does not directly influence sustainability, suggesting that intangible resources require digital financial mechanisms to generate measurable outcomes. Strategic Cost Management contributes indirectly by facilitating FinTech adoption. This study contributes to the dynamic capability literature by positioning Gender Innovation as an integrative capability linking inclusivity, knowledge resources, cost efficiency, and digital finance to sustainable MSME performance.